Nilai Humanisme Pada Film Elemental Forces of Nature - Handayani, Nur Afifah; Mayasari, Mayasari; Nayiroh, Luluatu (Jurnal Intervensi Sosial dan Pembangunan, 2024)
The film Elemental Forces of Nature is based on the experience of Peter Sohn as the director of the film. Peter Sohn is the son of a Korean immigrant family living in America, he and his family tried to survive in America by opening a shop in the Bronx. He poured this into his film, which tells the story of the struggles and challenges of an immigrant family (fire element) who are trying to survive in a city that has a different environment and culture from their place of origin. Ember (fire element) encounters many obstacles in maintaining the family business and her identity as a fire element but her friendship with Wade (water element) helps Ember to survive until the end. This study aims to determine the representation of humanism values contained in the film Elemental Forces of Nature. This study uses a qualitative method with Roland Barthes' semiotic analysis approach. Semiotics is a discipline or method of analysis that studies signs in the context of scenarios, images, texts, and film scenes that can be understood. Roland Barthes analyzes a meaning through three aspects, namely denotation, connotation, and myth. The results and conclusions of this study indicate that the denotation aspect describes the existence of humanism values in the film Elemental Forces of Nature, namely an attitude of tolerance, mutual respect, mutual respect, and mutual assistance, through the connotation aspect it is depicted that there is a warm family and friendship value with full tolerance, and an ideology that can be determined based on the myths in this film is shown by acculturation can unite differences.Keywords: Elemental Forces of Nature film, Peter Sohn, Humanism Values, Immigrant, and Semiotics